Impact of dose calculation accuracy during optimization on lung IMRT plan quality. (8th January 2015) - Li, Ying; Rodrigues, Anna; Li, Taoran; Yuan, Lulin; Yin, Fang‐Fang; Wu, Q. Jackie
Abstract : The purpose of this study was to evaluate the effect of dose calculation accuracy and the use of an intermediate dose calculation step during the optimization of intensity‐modulated radiation therapy (IMRT) planning on the final plan quality for lung cancer patients. This study included replanning for 11 randomly selected free‐breathing lung IMRT plans. The original plans were optimized using a fast pencil beam convolution algorithm. After optimization, the final dose calculation was performed using the analytical anisotropic algorithm (AAA). The Varian Treatment Planning System (TPS) Eclipse v11, includes an option to perform intermediate dose calculation during optimization using the AAA. The new plans were created using this intermediate dose calculation during optimization with the same planning objectives and dose constraints as in the original plan. Differences in dosimetric parameters for the planning target volume (PTV) dose coverage, organs‐at‐risk (OARs) dose sparing, and the number of monitor units (MU) between the original and new plans were analyzed. Statistical significance was determined with a p‐value of less than 0.05. All plans were normalized to cover 95% of the PTV with the prescription dose. Compared with the original plans, the PTV in the new plans had on average a lower maximum dose (69.45 vs. 71.96 Gy, p = 0.005 ), a better homogeneity index (HI) (0.08 vs. 0.12, p = 0.002 ), and a better conformity index (CI) (0.69 vs. 0.59, p = 0.003 ). In the new plans, lung sparing was increased as the volumes receiving 5, 10, and 30 Gy were reduced when compared to the original plans (40.39% vs. 42.73%, p = 0.005 ; 28.93% vs. 30.40%, p = 0.001 ; 14.11% vs. 14.84%, p = 0.031 ). The volume receiving 20 Gy was not significantly lower (19.60% vs. 20.38%, p = 0.052 ). Further, the mean dose to the lung was reduced in the new plans (11.55 vs. 12.12 Gy, p = 0.024 ). For the esophagus, the mean dose, the maximum dose, and the volumes receiving 20 and 60 Gy were lower in the new plans than in the original plans (17.91 vs. 19.24 Gy, p = 0.004 ; 57.32 vs. 59.81 Gy, p = 0.020 ; 39.34% vs. 41.59%, p = 0.097 ; 12.56% vs. 15.35%, p = 0.101 ). For the heart, the mean dose, the maximum dose, and the volume receiving 40 Gy were also lower in new plans (11.07 vs. 12.04 Gy, p = 0.007 ; 56.41 vs. 57.7 Gy, p = 0.027 ; 7.16% vs. 9.37%, p = 0.012 ). The maximum dose to the spinal cord in the new plans was significantly lower than in the original IMRT plans (29.1 vs. 31.39 Gy, p = 0.014 ). Difference in MU between the IMRT plans was not significant (1216.90 vs. 1198.91, p = 0.328 ). In comparison to the original plans, the number of iterations needed to meet the optimization objectives in the new plans was reduced by a factor of 2 (2–3 vs. 5–6 iterations). Further, optimization was 30% faster corresponding to an average time savings of 10–15 min for the reoptimized plans. Accuracy of the dose calculation algorithm during optimization has an impact on planning efficiency, as well as on the final plan dosimetric quality. For lung IMRT treatment planning, utilizing the intermediate dose calculation during optimization is feasible for dose homogeneity improvement of the PTV and for improvement of optimization efficiency. PACS numbers: 87.55.D‐, 87.55.de, 87.55.dk